2016
DOI: 10.3389/fnhum.2016.00644
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Representations and Brain Asymmetry during the Processing of Autobiographical Emotional Memories in Late Adolescence

Abstract: Frontal and parietal asymmetries have repeatedly been shown to be related to specific functional mechanisms involved in emotion regulation. From a developmental perspective, attachment representations based on experiences with the caregiver are theorized to serve regulatory functions and influence how individuals deal with emotionally challenging situations throughout the life span. This study aimed to investigate neural substrates of emotion regulation by assessing state- and trait dependent EEG asymmetries i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…The effect of regionally specific brain activation corresponds to the results of the emotional memory study, which showed that both the degree of such activation and its lateral features depend on the individual characteristics of memory strategies [26] and the psychometrically assessed self-confidence in the choice of behavior style [27]. EEG asymmetries are modulated by both the induction of certain emotions and individual affective dispositions [2].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The effect of regionally specific brain activation corresponds to the results of the emotional memory study, which showed that both the degree of such activation and its lateral features depend on the individual characteristics of memory strategies [26] and the psychometrically assessed self-confidence in the choice of behavior style [27]. EEG asymmetries are modulated by both the induction of certain emotions and individual affective dispositions [2].…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, in the future, it is necessary to determine which personality traits (for example, a disposition to use approach/avoidance strategies, emotional intelligence, or neuroticism) make the most significant contribution to this effect of individual variability in EEG correlates of emotional autobiographical memory. Indeed, it was found that attachment representations differentially affect the parietal organization of hemispheric asymmetry during the retrieval of emotional memories [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attachment-related processing involves prefrontal and orbito-frontal as well as occipital areas in both hemispheres 35 , 36 . Nevertheless, neural circuits in the right prefrontal and orbito-frontal cortex might be more important for emotional evaluation of attachment relevant stimuli compared with homologue areas in the left hemisphere as found in earlier work 37 40 explaining why correlations with attachment anxiety and valence were only significant for the right frontal ERP effect.…”
Section: Discussionmentioning
confidence: 69%
“…Since lateralization of sleep spindles was found to correlate with asymmetric involvement of hemispheres during online information processing in case of memory tasks (Nishida & Walker, 2007), we assume that it can also apply to certain trait-like dispositions in cognitive-emotional functioning that appear to show specific lateralization patterns as well (Harmon-Jones & Gable, 2018;Herrington et al, 2009;Kungl et al, 2016;Moshirian Farahi et al, 2019). We hypothesize that relative left domination of frontal slow spindle lateralization correlates negatively with psychological traits that are argued to be related to enhanced right or reduced left hemispheric frontal activity, namely attachment anxiety and trait-like emotional reactivity indexed by neuroticism.…”
Section: Introductionmentioning
confidence: 99%